1982
DOI: 10.1021/j100394a030
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational energy transfer in laser-excited carbonic difluoride. Infrared fluorescence from the intermediate mode .nu.4

Abstract: quasicontinuum") are less important at least up to n = 5 than direct twoor three-photon transitions. The evidence was as follows: (1) excitation by P10 or P16, where the first step has to be a two-photon transition, generates similar effects as observed at other wavelengths in flash spectroscopy; (2) the dissociation yield strongly depends at all investigated wavelengths on the laser intensity, indeed stronger than expected for an explanation invoking hole burning in the rotational contour; (3) the carbon isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Intermolecular interactions involving carbonyl fluoride are of interest since this compound is believed to be one of the intermediates in the photodecomposition of chlorofluorocarbons in the stratosphere. , Another motivation of the study is that COF 2 is often observed in matrix-isolation infrared experiments as a product of photolysis of various fluorine-containing compounds. Since the formation of COF 2 is sometimes accompanied by its complexation, , knowledge of structures and energies of plausible complexes is important for interpreting the observed spectra. In addition, it may be noted that COF 2 is one of the simplest asymmetric top molecules which has been widely used for testing various theoretical models of vibrational spectroscopy. It appears interesting to correlate the complexation effect on vibrational spectra with some of the theoretical predictions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermolecular interactions involving carbonyl fluoride are of interest since this compound is believed to be one of the intermediates in the photodecomposition of chlorofluorocarbons in the stratosphere. , Another motivation of the study is that COF 2 is often observed in matrix-isolation infrared experiments as a product of photolysis of various fluorine-containing compounds. Since the formation of COF 2 is sometimes accompanied by its complexation, , knowledge of structures and energies of plausible complexes is important for interpreting the observed spectra. In addition, it may be noted that COF 2 is one of the simplest asymmetric top molecules which has been widely used for testing various theoretical models of vibrational spectroscopy. It appears interesting to correlate the complexation effect on vibrational spectra with some of the theoretical predictions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it may be noted that COF 2 is one of the simplest asymmetric top molecules which has been widely used for testing various theoretical models of vibrational spectroscopy. [24][25][26][27][28] It appears interesting to correlate the com- plexation effect on vibrational spectra with some of the theoretical predictions.…”
Section: Introductionmentioning
confidence: 99%